An experimental investigation on mechanical performances of 3D printed lightweight ABS pipes with different cellular wall thickness - Ergene, B.; Sekeroglu, I.; Bolat, C.; Yalcin, B. (Universiti Malaysia Pahang Al-Sultan Abdullah Press (UMPSA Press), 2021)
In recent years, cellular structures have attracted great deal of attention of many researchers due to their unique properties like exhibiting high strength at low density and great energy absorption. Also, the applications of cellular structures (or lattice structures) such as wing airfoil, tire, fiber and implant, are mainly used in aerospace, automotive, textile and biomedical industries respectively. In this investigation, the idea of using cellular structures in pipes made of acrylonitrile butadiene styrene (ABS) material was focused on and four different pipe types were designed as honeycomb structure model, straight rib pattern model, hybrid version of the first two models and fully solid model. Subsequently, these models were 3D printed by using FDM method and these lightweight pipes were subjected to compression tests in order to obtain stress-strain curves of these structures. Mechanical properties of lightweight pipes like elasticity modulus, specific modulus, compressive strength, specific compressive strength, absorbed energy and specific absorbed energy were calculated and compared to each other. Moreover, deformation modes were recorded during all compression tests and reported as well. The results showed that pipe models including lattice wall thickness could be preferred for the applications which don’t require too high compressive strength and their specific energy absorption values were notably capable to compete with fully solid pipe structures. In particular, rib shape lattice structure had the highest elongation while the fully solid one possessed worst ductility. Lastly, it is pointed out that 3D printing method provides a great opportunity to have a foresight about production of uncommon parts by prototyping.
Keywords: Design; deformation mechanism; d printing; Mechanics of engineering. Applied mechanics; Composite; D printing; TA349-359; mechanical performance; Fabrication; TJ1-1570; Cellular structure; Mechanical engineering and machinery; energy absorption; cellular structure